2020
DOI: 10.1111/jasp.12696
|View full text |Cite
|
Sign up to set email alerts
|

Procedural fairness enacted by societal actors increases social trust and social acceptance among ethnic minority members through the promotion of sense of societal belonging

Abstract: overviews). When an authority makes a decision that affects someone, people are inclined to assess its fairness or unfairness. These fairness perceptions may have pervasive effects on people's attitudes, values, and behavior (Tyler & Blader, 2003), ultimately having a profound impact on how they feel and react within the context of their social groups (De Cremer & Tyler, 2005; Tyler & Lind, 1992). Fairness has long been considered mainly in terms of distributive fairness, referring to the perception of fairnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 73 publications
(150 reference statements)
8
26
0
Order By: Relevance
“…Previous theorizing on procedural fairness processes emphasized processes within groups and more particularly focused on the social relationship between the individual group member who receives procedural fairness and the authority figure enacting it (see Valcke et al, 2020). This was also the case in the scant procedural fairness studies that involved minorities, which pertained to situations in which the individual minority member was being (not) granted fairness (see Huo, Smith, Tyler & Lind, 1996;Huo & Tyler, 2000.…”
Section: Procedural Fairness and Identification: Importance For Ethnic Minoritiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous theorizing on procedural fairness processes emphasized processes within groups and more particularly focused on the social relationship between the individual group member who receives procedural fairness and the authority figure enacting it (see Valcke et al, 2020). This was also the case in the scant procedural fairness studies that involved minorities, which pertained to situations in which the individual minority member was being (not) granted fairness (see Huo, Smith, Tyler & Lind, 1996;Huo & Tyler, 2000.…”
Section: Procedural Fairness and Identification: Importance For Ethnic Minoritiesmentioning
confidence: 99%
“…Societal institutions (e.g., courts, school boards, community councils, the police, the political system, and so on) can thus be regarded as superordinate enacting authorities. Moreover, given that these authorities make decisions about minority members on a daily basis in a broad number of domains, they can be considered as potentially important enactors of procedural fairness as well (see Valcke et al, 2020). Valcke et al (2020) have already shown that the perceived fairness of decisionmaking processes of societal actors increased the sense of (societal) belongingness of ethnic minorities.…”
Section: Procedural Fairness and Identification: Importance For Ethnic Minoritiesmentioning
confidence: 99%
See 3 more Smart Citations